Technical-economic analysis of a hydrogen production facility for power-to-gas and hydrogen mobility under different renewable sources in Southern Italy. (1st November 2020) - Fragiacomo, Petronilla; Genovese, Matteo
Graphical abstract: Highlights: Sizing of three hydrogen infrastructures for 287, 180 and 22 kg of daily production. The efficiency resulted to be up to 57.5% and a consumption of 58.2 kWh/kg. Renewable energy penetration is analyzed for each source and location. Sensitive analysis ranging the hydrogen mobility and injections share. Emission cut could lead to 1100 k€ of health-savings in 20 years. Abstract: Hydrogen facilities are worldwide recognized as decarbonizing energy systems, but strategic actions are needed by intensifying the effort on the feasibility studies concerning the integration of multiple hydrogen systems, to foster and accelerate the achievement of the break-even points. The present paper proposes a comprehensive technical-economical assessment of PEM hydrogen production system via water electrolysis, in three different Southern Italian locations powered by grid electricity and renewable energies, namely wind, solar, geothermal. Hydrogen is then stored in gaseous form at 350 bar. The generated hydrogen in each facility is used to meet two different end-users needs: hydrogen mobility and hydrogen injections in the natural gas grid/pipelines. Hydrogen-to-mobility serves fuel cell electric vehicles, requiring high-pressure delivery and dispensing up to 700 bar, while for hydrogen injections, a double-stage pressure reducer is considered, by stepping down the pressure level at 50 bar. The financial investigation has been based on two main sensitive analysis: a power-purchase agreement price ranging from 50 to 100 €/MWh, and several scenarios for the hydrogen end-users, by ranging the potential hydrogen delivery from 25 to 100% of the daily production for the Hydrogen Mobility. As a novelty, the present paper integrates an emission analysis, in order to take into account the carbon footprint of these innovative applications and their benefits related to health and quality of life in terms of economic repercussions on society.